Milimeter-wave bandpass filter for radio over fiber application - Muhammad, Siti Najwa (2014)
Radio over fiber (RoF) technology is a promising option to deliver high speed broadband networks as it capable of delivering high data rate transmission, has low attenuation, immune to radio frequency interference (RFI) and simple design of remote antenna unit (RAU). Milimeter-wave on the other hand is in the range 30 GHz to 300 GHz and offers higher bandwidth compared to lower RF frequency. The adoption of millimeter-wave in RoF technology will enhance its ability to deliver high speed broadband by utilizing the benefits of RoF and millimeter-wave. Millimeter-wave bandpass filter has been design in this project for frequency range of 40 GHz to 42 GHz as part of the RAU design. The designed bandpass filter will be fabricated using low temperature co-fired ceramic (LTCC) technology that will enable compact and flexible bandpass filter design.